A Polyaromatic Gemini Amphiphile That Assembles into a Well‐Defined Aromatic Micelle with Higher Stability and Host Functions. (4th April 2019) - Nishioka, Tomoya; Kuroda, Kiyonori; Akita, Munetaka; Yoshizawa, Michito
Abstract: A gemini‐type amphiphilic molecule, constituted of two V‐shaped polyaromatic amphiphiles linked by a linear acetylene spacer, was synthesized. The gemini amphiphile assembles into a well‐defined aromatic micelle (ca. 2 nm in core diameter), providing higher stability in water even at low concentration (0.09 mm ) and high temperature (>130 °C). Unlike common gemini amphiphiles with aliphatic chains, the present amphiphile and its micellar assembly emit green and orange fluorescence ( Φ F =33 and 9 %), respectively. Despite strong and multiple π‐stacks of the polyaromatic panels of the amphiphiles, the water‐soluble gemini aromatic micelle incorporates medium‐size to large hydrophobic compounds into the frameworks. Interestingly, the guest binding capability toward large planar molecules was enhanced by more than two times through the pre‐encapsulation of spherical molecules in the cavity. Abstract : Ein Gemini‐artiges polyaromatisches amphiphiles Molekül ordnet sich in Wasser zu klar definierten aromatischen Mizellen mit hoher Stabilität an. Die Gemini‐Mizellen nehmen dabei mittlere bis große hydrophobe Moleküle in ihre Gerüste auf. Die Möglichkeiten zur Gast‐Bindung großer planarer Moleküle werden durch die Vor‐Einkapselung sphärischer Moleküle in den Hohlraum signifikant erweitert.